Phosphoproteomic analysis reveals that PP4 dephosphorylates KAP-1 impacting the DNA damage response - Lee, Dong-Hyun (Nature Publishing Group, 2012)
Protein phosphatase PP4C has been implicated in the DNA damage response (DDR), but its substrates in DDR remain largely unknown. We devised a novel proteomic strategy for systematic identification of proteins dephosphorylated by PP4C and identified KRAB-domain-associated protein 1 (KAP-1) as a substrate. Ionizing radiation leads to phosphorylation of KAP-1 at S824 (via ATM) and at S473 (via CHK2). A PP4C/R3β complex interacts with KAP-1 and silencing this complex leads to persistence of phospho-S824 and phospho-S473. We identify a new role for KAP-1 in DDR by showing that phosphorylation of S473 impacts the G2/M checkpoint. Depletion of PP4R3β or expression of the phosphomimetic KAP-1 S473 mutant (S473D) leads to a prolonged G2/M checkpoint. Phosphorylation of S824 is necessary for repair of heterochromatic DNA lesions and similar to cells expressing phosphomimetic KAP-1 S824 mutant (S824D), or PP4R3β-silenced cells, display prolonged relaxation of chromatin with release of chromatin remodelling protein CHD3. Our results define a new role for PP4-mediated dephosphorylation in the DDR, including the regulation of a previously undescribed function of KAP-1 in checkpoint response.